Understanding practice placements where students falter and fail: A theoretical exposition of critical realism for social work practice education - Flynn, Susan (My University, 2023)
This paper offers a theoretical exposition of critical realism for social work practice education. The specific focus is on faltering students at the cusp of placement failure, and the urgent supportive role of practice educators and tutors in promoting learner’s reflective capacity as active agents in their learning. A key premise of the paper is that eliminating the oftentimes contested space between what key parties think is happening, and what is actually manifest in reality, is an imperative that can be supported by critical realism. Here critical realist scholars argue that one’s social reality is manifest in proximity to both an observable and socially constructed world, alongside an actual real world, with the former sometimes at odds with the latter. As the placement falters, key social actors such as practice teachers and college tutors urgently strive to make sense of conditions of possibility for student failure and to reach social consensus about the reality that underpins the speculative boundaries of student competency. Here critical realism can render visible the very ontology of practice. Whilst there are already theoretical mainstays to guide understanding of social work practice education, such as models of critical reflection and reflective practice, these are arguably limited in at least one key respect. They attend to the intersection of student’s espoused theories of their behaviour, and their actual practice reality, but fail to afford meaningful attention to the ontological nature of reality as socially interpreted in social work. Here the case is made for critical realism as a theoretical tool for practice education with students who falter and fail.
PUBLISHED
https://journals.whitingbirch.net/index.php/JPTS/issue/view/194
Keywords: Critical realism; Placement; Failure; Social work; Field education